2008
DOI: 10.1038/pcan.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of prostate cancer in male breast cancer patients: a risk factor for prostate cancer screening

Abstract: Synchronous or metachronous occurrences of both prostate cancer and male breast cancer are rarely reported, but provide insight into their hormonal and genetic biology. We sought to determine the incidence of prostate cancer in male breast cancer patients at our institution, and to examine estrogen receptor (ER), progesterone receptor (PR) and HER-2/neu receptor (HR) status in these patients. A retrospective review was conducted of male breast cancer patients from 1990 to 2006. Histopathologic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
(27 reference statements)
0
29
1
Order By: Relevance
“…Although we could not evaluate previous suggestions of an increased risk of male breast cancer associated with a personal history of prostate cancer (39,40) because of our reliance on a initial diagnosis of cancer to define cases of male breast cancer in this study, we found no support that either prostatic hypertrophy or dysplasia were associated with risk. We did, however, observe a significant association of male breast cancer risk with a history of orchitis or epididymitis.…”
Section: Discussioncontrasting
confidence: 77%
“…Although we could not evaluate previous suggestions of an increased risk of male breast cancer associated with a personal history of prostate cancer (39,40) because of our reliance on a initial diagnosis of cancer to define cases of male breast cancer in this study, we found no support that either prostatic hypertrophy or dysplasia were associated with risk. We did, however, observe a significant association of male breast cancer risk with a history of orchitis or epididymitis.…”
Section: Discussioncontrasting
confidence: 77%
“…A review of 69 patients with MBC identified 12 patients (17%) with concomitant diagnoses of prostate cancer. 18 A theoretical link between these diseases does exist – for example, aromatase inhibitors used to treat MBC may increase serum levels of testosterone, thereby driving growth and proliferation of prostate cancer clones. 19 Although further prospective testing is needed to validate this association, the practitioner may choose to weigh this data in the risk: benefit decision to initiate prostate cancer screening in patients with MBC.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Typically men with breast cancer have a longer duration of symptoms than women [12]. With a lack of awareness and the advanced stage at presentation, such delay in diagnosis often causes a worse prognosis than FBC [13]. Consequently MBC patients have a mortality of 5-10 years in 36-75% of cases [13].…”
Section: Introductionmentioning
confidence: 99%